2018
DOI: 10.2174/1389203719666180508111843
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Dietary Fibre with Nutritional Components on Gut Microbial Composition, Function and Health in Monogastrics

Abstract: The relation between dietary fibre and the well-being of human and other monogastrics has recently became a hot topic as shown by the increasing number of publications of the related research. The aim of this review is to describe - through a logical approach - the scientific suggestion linking possible benefits of dietary fibre on nutritional components and their effect on the gastrointestinal composition in relation to disease conditions in humans and animals. Dietary fibre plays a key role in: influencing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The mechanism through by a low concentration of POM increased nutrient digestibility is unclear. However, it was well established that mushrooms contain high fibre content and these dietary fibres may decrease intestinal transit time and hence account for its effect on nutrient digestibility …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism through by a low concentration of POM increased nutrient digestibility is unclear. However, it was well established that mushrooms contain high fibre content and these dietary fibres may decrease intestinal transit time and hence account for its effect on nutrient digestibility …”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota contains over 10 14 microbial cells that collectively comprise at least 150 times more genes than their host. 1,2 The composition of the gut microbiota in humans and other monogastric animals varies based on age, diet, genetic characteristics, and sex. 1 Gut microbiota have some important functions in host health, nutrient metabolism and absorption, development of the host immune system, differentiation of the gut epithelium, and maintenance of the gut mucosal barrier functions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The composition of the gut microbiota in humans and other monogastric animals varies based on age, diet, genetic characteristics, and sex. 1 Gut microbiota have some important functions in host health, nutrient metabolism and absorption, development of the host immune system, differentiation of the gut epithelium, and maintenance of the gut mucosal barrier functions. 3,4 Previous evidence indicated that gut microorganisms can directly inuence physiological conditions in animals such as improving the roles of the intestinal barrier, stimulating defence mechanisms against pathogens, improving the host immune system, increasing defensive mechanisms against inammatory bowel diseases (IBD), 5 regulating autoimmunity, producing biological metabolites, preventing obesity and regulating diabetes, and destroying cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations